Penerapan Metode Demonstrasi dalam Pembelajaran Khat untuk Meningkatkan Keterampilan Menulis Siswa - Mujahida, Mujahida; Bachtiar, Fauziah; Alamsyah, Alamsyah (FONDATIA, 2025)
This study was motivated by the limited research on the application of the demonstration method in khat (Arabic calligraphy) instruction at the Madrasah Tsanawiyah level. It aims to examine the planning, implementation, and outcomes of using the demonstration method in khat lessons to improve students’ Arabic writing skills. The research employed Classroom Action Research (Penelitian Tindakan Kelas [PTK]) conducted in two cycles, each consisting of two meetings, with 30 Grade IX students of MTs DDI Ujung as the subjects. The independent variables in this study were the demonstration method and khat instruction, while the dependent variable was Arabic writing skill. Data were collected through observation to obtain qualitative data and evaluation tests to obtain quantitative data. The results show that lesson plans were systematically designed, and their implementation enhanced interaction between teacher and students. The average student evaluation score increased from 71% in the first cycle to 84% in the second cycle, representing a 13% improvement. These findings confirm that the application of the demonstration method in khat instruction is effective in significantly improving students’ Arabic writing skills.